Hybrid Cryptography security in public cloud using TwoFish and ECC algorithm - Siva Sankaran P.; Kirubanand V B (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Cloud computing is a structure for rendering service to the user for free or paid basis through internet facility where we can access to a bulk of shared resources which results in saving managing cost and time for large companies, The data which are stored in the data center may incur various security, damage and threat issues which may result in data leakage, insecure interface and inside attacks. This paper will demonstrate the implementation of hybrid cryptography security in public cloud by a combination of Elliptical Curve Cryptography and Twofish algorithm, which provides an innovative solution to enhance the security features of the cloud so that we can improve the service thus results in increasing the trust over the technology.